STAC3 gene congenital myopathy and malignant hyperthermia: a crossroads between neurology and anesthesia - Silva, Mary Santos; Nakamura, Ricardo; Arjona, Marcia Rosana; Monaco, Thue Peres Colferai Del; Malito, Mauricio Luiz; Sampaio, Taís Oliveira; Oliveira, Samantha Lopes de; Magalhães, Juliana Silva de Almeida; Machado-Costa, Marcela Camara; Silva, Helga Cristina Almeida (Arquivos de Neuro-Psiquiatria, 2025)
STAC3 gene congenital myopathy and malignant hyperthermia (MH) represent an important crossroads between neurology and anesthesia, where the prompt recognition of the clinical characteristics, and the collaboration between neurologists and anesthesiologists, are essential to early diagnosis and prevention of adverse critical events. This gene is associated with a congenital myopathy first reported as Native American myopathy (NAM), a rare condition characterized by dysmorphisms, contractures, muscular complaints, and scoliosis. As a rare pharmacogenetic hypermetabolic disease, MH is triggered by halogenated agents and/or succinylcholine, linked to variants in the RYR1,CACNA1S, or STAC3 genes. Our objective was to analyze the characteristics of a Brazilian case series of STAC3 gene myopathy associated with MH and to review previous reports. We report three MH crises, in two boys and one girl, 2 to 15 years old. All of them received halogenated agents and one additionally received succinylcholine. Two patients presented two to four previous uneventful general anesthesia. The MH crises in this series of patients with STAC3 gene mutations demonstrated variable clinical characteristics (expressivity) and occurrence (penetrance). Neuromuscular patients with findings suggestive of STAC3 myopathy should increase diagnostic suspicion regarding the risk of MH. Conversely, the careful evaluation of the anesthetic antecedents of neuromuscular patients can help to restrict the candidate genes. Additionally, Brazilian neurologists can notify neurological patients with antecedents of adverse events during anesthesia to the Brazilian Registry of Neurological Diseases (Registro Brasileiro de Doenças Neurológicas, REDONE, in Portuguese).
Keywords: Anesthesia; Malignant Hyperthermia; Muscular Diseases